Association of ABCB1 and MTHFR genetic polymorphisms with rheumatoid arthritis susceptibility in a Chinese population - Chen, Yanfei; Wu, Jirong; Dong, Qiaomei; Li, Juan (Frontiers in Medicine, 2025)
ObjectiveThe present study aimed to investigate the association of the ATP-binding cassette subfamily B member 1 (ABCB1) 3435C/T and methylenetetrahydrofolate reductase (MTHFR) 677C/T and 1298A/C polymorphisms with susceptibility to RA and RA subtype.MethodsWe enrolled 85 RA patients and 45 healthy individuals in this study. Genotyping for ABCB1 3435C/T, MTHFR 677C/T and 1298A/C was performed using fluorescence in situ hybridization technology (FISH).ResultsNo significant differences in the genotype and allele frequency distributions of ABCB1 3435C/T, MTHFR 1298A/C or MTHFR677C/T were detected between patients with RA and healthy individuals (p > 0.05). Logistic regression analysis, after adjusting for sex and age, showed that the MTHFR677C/T TT genotype was associated with increased susceptibility to RA compared with the CC genotype (TT versus CC, p = 0.034, OR = 2.316; 95%CI = 1.067–5.029); however, after Bonferroni correction, the association between the MTHFR677C/T TT genotype and RA susceptibility was no longer significant. That MTHFR 677C/T genotype frequency (CT versus CC, p = 0.040, OR = 6.504; 95% CI = 1.087–38.935) and dominant model (CT+TT versus CC, p = 0.025, OR = 6.556; 95% CI = 1.272–33.799) was associated with ACPA status among RA patients; and that MTHFR 677C/T genotype frequency (TT versus CC, p = 0.044, OR = 2.171; 95% CI = 1.020–4.623) and codominant model (CC versus CT versus TT, p = 0.026, OR = 2.059; 95% CI = 1.089–3.891) were associated with RF status among RA patients; Similarly, the associations observed in ACPA-positive and RF-positive subgroups also lost significance after Bonferroni correction.ConclusionThe MTHFR 677C/T polymorphism may be associated with susceptibility to RA and RA subtypes; ABCB1 3435C/T and MTHFR 1298A/C were not associated with the susceptibility to RA or RA subtypes.